Barrow holographic dark energy with varying exponent - Spyros Basilakos; Andreas Lymperis; Maria Petronikolou; Emmanuel N. Saridakis (Nuclear Physics B)
We construct Barrow holographic dark energy with varying exponent. Such an energy-scale-dependent behavior is typical in quantum field theory and quantum gravity under renormalization group considerations, however in the present scenario it has an additional justification, since in realistic cases one expects that Barrow entropy quantum-gravitational effects to be stronger at early times and to smooth out and disappear at late times. We impose specific, redshift-dependent ansätze for the Barrow running exponent, such as the linear, CPL-like, exponential, and trigonometric ones, and we investigate their cosmological behavior. We show that we can recover the standard thermal history of the universe, with the sequence of matter and dark energy epochs, in which the transition from deceleration to acceleration happens at z≈0.65, in agreement with observations. In the most realistic case of hyperbolic tangent ansatz, in which we can easily bound Barrow exponent inside its theoretically determined bounds 0 and 1 for all redshifts, we see that the dark-energy equation-of-state parameter can be quintessence like, or experience the phantom-divide crossing, while in the future it can either tend to the cosmological constant value or start increasing again. All these features reveal that Barrow holographic dark energy with varying exponent is not only theoretically more justified than the standard, constant-exponent case, but it leads to richer cosmological behavior too.